Inheritance of some reproductive traits by young bulls - Warren, J.H.; Blum, J.; Schalles, R.R.; Kiracofe, G.; Henry, K.; Hultine, V. (Kansas State University. Agricultural Experiment Station, 2011)
Severa1 reproductive traits of yearling Polled Hereford bulls were evaluated during and immediately after a 140-day feeding test. Results indicate that concentration of sperm and percentages of live sperm are heritable and genetically independent of each other. Heritability was low for sex drive or libido.
1776-1976 "Buffalo to Beef" is known as Cattlemen’s Day, 1976
Keywords: Beef; Reproductive traits; Heritability; Libido